Perencanaan dan Implementasi SAP pada PT XYZ dengan Menggunakan Metode Accelerated SAP (ASAP) - Maulidina, Rahma; Rizki, Nur Anisa; Dewi, Renny Sari (STMIK Budi Darma, 2020)
An integrated information system is a need to help solve problems in managing business transactions. SAP application is one application that is able to provide solutions to these problems. The purpose of writing this research is to plan running business processes, plan implementation of the current SAP system related to the implementation and maintenance of SAP applications and provide development suggestions based on the results of planning obtained, in terms of business processes, performance, and financial. For the analysis, the IT Balanced Scorecard method is used, while for system development the ASAP (Accelerated SAP) methodology is used. This research produces an analysis of the planning of the company's business processes in implementing the implementation of the SAP financial and controlling ERP.